Effect of nutrition education with the principles of Diabetes Self-Management Education (DSME) on knowledge and physical activity of type 2 diabetes patients - Raden Rizqia Khansa (UHAMKA PRESS, 2020)
Diabetes mellitus (DM) is one of the most critical illnesses experienced worldwide. Pillars for the management of type 2 DM are education, medical nutrition therapy, physical exercise, and pharmacological interventions. This study aimed to analyze Diabetes Self-Management Research (DSME) on the level of knowledge and activities of type II DM patients in Fatmawati General Hospital, South Jakarta. This research method used pre-experimentation with one group pretest-posttest. Analysis of the data used in univariate and bivariate analysis with a paired t-test. Sampling method was using a consecutive sampling technique obtained by 23 subjects. The results of the study showed differences between the previous and conducted DSME on the level of knowledge (p<0.001) and the level of physical activity (p=0.001). Based on the results of this study, there needs to be an improvement in the curriculum with support materials related to stress and the healthcare system.